Stress as the Dominant Factor of Hypertension - Rd. Halim; Ledy Uli Vidi Gultom; Hendra Dhermawan Sitanggang (PT FORMOSA CENDEKIA GLOBAL, 2022)
Hypertension is one of the non-communicable diseases (NCD) which became a major public health problem both in Indonesia and in the world. Data from the Public Health Office of Jambi showed that hypertension rate was 11.33% in 2019, 3.15% in 2020 and 4.00% in 2021. This study aimed to determine the factors associated with the incidence of hypertension at the Paal Lima Public Health Centre of Jambi City. This study used a cross-sectional design with 214 respondents aged ≥ 18 years old selected through accidental sampling. Data were analysed through chi-square test for bivariate analysis and cox regression for multivariate analysis. The prevalence of hypertension in the study was 33.2%. The multivariate analysis indicated that age (aPR= 2.502; 95% CI: 1.302 to 4.809), salt consumption (aPR= 1.799; 95% CI: 1.086 to 2.978), and stress (aPR= 3.963; 95% CI: 2.355 to 6,670) were correlated with the incidence of hypertension. Age, salt consumption, and stress were the risk factor of the incidence of hypertension. The most dominant factor affecting the incidence of hypertension was stress. Therefore, stress managements are required to reduce stress experienced by people apart from consuming low-sodium food.